2016
DOI: 10.1152/jn.00834.2015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic imaging of movement-related Purkinje cell calcium activity in awake behaving mice

Abstract: Gaffield MA, Amat SB, Bito H, Christie JM. Chronic imaging of movement-related Purkinje cell calcium activity in awake behaving mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 68 publications
5
32
1
Order By: Relevance
“…CF responses in Crus I were not due to motor action as sensory-related activity persisted under anesthesia-induced paralysis. In previous studies, we also observed lobule-specific differences in the representation of behavioral variables, with orofacial movements in response to reward consumption engaging neurons in Crus II but not Crus I (Gaffield et al, 2016;Gaffield and Christie, 2017). Combined, these results suggest partitioned representations of unpredicted sensations and mechanics of action within the lateral posterior hemispheres, cerebellar regions increasingly implicated in cognitive function in both humans and mice (Deverett et al, 2018;Schmahmann, 2018;Stoodley et al, 2017).…”
Section: Pc Dendrites Broadly Encode the Occurrence Of Sensory Stimulsupporting
confidence: 71%
See 3 more Smart Citations
“…CF responses in Crus I were not due to motor action as sensory-related activity persisted under anesthesia-induced paralysis. In previous studies, we also observed lobule-specific differences in the representation of behavioral variables, with orofacial movements in response to reward consumption engaging neurons in Crus II but not Crus I (Gaffield et al, 2016;Gaffield and Christie, 2017). Combined, these results suggest partitioned representations of unpredicted sensations and mechanics of action within the lateral posterior hemispheres, cerebellar regions increasingly implicated in cognitive function in both humans and mice (Deverett et al, 2018;Schmahmann, 2018;Stoodley et al, 2017).…”
Section: Pc Dendrites Broadly Encode the Occurrence Of Sensory Stimulsupporting
confidence: 71%
“…Time-series images of Ca 2+ activity in neurons expressing genetically encoded Ca 2+ indicators were aligned using a least-squares algorithm. PCs and CFs were segmented using an independent component analysis algorithm to group like-responding pixels (Hyvarinen, 1999) and Ca 2+ events identified using an inference-based method (Gaffield et al, 2016;Vogelstein et al, 2010). Ca 2+ event rates were calculated from each image (34 ms in duration).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two approaches for delivering light to the brain are to either implant a light fiber, or to create a cranial window that provides optical access to the underlying cortex. The fiber-based approach can target subcortical structures that are not accessible via cranial windows (Aravanis et al, 2007;Gaffield et al, 2015), and can sample a field of view as large as 2 mm with the use of head-mounted microendoscopes (Jennings et al, 2015). However, mesoscopic mapping of cortical function-a spatial scale where the relationship among several functional regions can be examined (Oh et al, 2014;Silasi and Murphy, 2014) -requires optical access to an even larger area, with preferably non-invasive preparations to resolve map-like activity.…”
Section: Introductionmentioning
confidence: 99%